Protective effect of a combined glutathione and prednisolone administration on mice subjected to a lipopolysaccharide-induced cytokine storm - H. Al-Rajhi, Shaymaa; Hamood, Heba Majed; Shihab, Elaf Mahmood; Shareef, Saja Majeed; Ridha-Salman, Hayder; Salim Shahooth, Samer; Attarbashee, Rana Khairi; Abbas, Alaa Hamza; Adham, Lina Sami; Hasan Al-Bairmani, Rana Jawad; et al. (Pharmakeftiki, 2025)
Cytokine storm is a life-threatening hyperinflammatory condition that can result from infectious diseases, including COVID-19, as well as from non-infectious autoimmune disorders. This study has investigated the potential of glutathione to mitigate a cytokine storm in mice, particularly when administered in combination with prednisolone; a synthetic glucocorticoid. Fifty male albino mice were randomly assigned into five groups. The negative control group received 1% dimethyl sulfoxide (DMSO) intraperitoneally (i.p.), while the positive control group received a single i.p. dose of lipopolysaccharide (LPS) at 5 mg/kg. The treatment groups received either glutathione (200 mg/kg i.p.), prednisolone (5 mg/kg i.p.), or a combination of both drugs, each administered as a single dose, 1 h prior to the LPS injection. After 24 h, blood samples were collected in order to assess the serum interleukin-6 (IL-6) levels, and lung tissues were harvested for histopathological analysis. The results demonstrated that glutathione, prednisolone, and their combination can significantly reduce the LPS-induced elevation of IL-6 levels (p<0.05) and can ameliorate the LPS-induced histopathological damage in the lung tissues of mice. In conclusion, pre-treatment with glutathione, prednisolone, or their combination can effectively attenuate both the systemic IL-6 elevation and the pulmonary histopathological alterations associated with cytokine storm. Notably, the combined administration of glutathione and prednisolone exhibited synergistic protective effects, suggesting their potential utility as prophylactic agents against cytokine storm syndromes.